Ultrasensitive Electroanalytical Detection of Pb2+ and H2O2 Using Bi and Fe—Based Nanoparticles Embedded into Porous Carbon Xerogel—The Influence of Nanocomposite Pyrolysis Temperatures - Mihai M. Rusu; Carmen I. Fort; Adriana Vulpoi; Lucian Barbu-Tudoran; Monica Baia; Liviu C. Cotet; Lucian Baia (Gels, 2023)
Multifunctional materials based on carbon xerogel (CX) with embedded bismuth (Bi) and iron (Fe) nanoparticles are tested for ultrasensitive amperometric detection of lead cation (Pb2+) and hydrogen peroxide (H2O2). The prepared CXBiFe-T nanocomposites were annealed at different pyrolysis temperatures (T, between 600 and 1050 °C) and characterized by X-ray diffraction (XRD), Raman spectroscopy, N2 adsorption, dynamic light scattering (DLS), and electron microscopies (SEM/EDX and TEM). Electrochemical impedance spectroscopy (EIS) and square wave anodic stripping voltammetry (SWV) performed at glassy carbon (GC) electrodes modified with chitosan (Chi)-CXBiFe-T evidenced that GC/Chi-CXBiFe-1050 electrodes exhibit excellent analytical behavior for Pb2+ and H2O2 amperometric detection: high sensitivity for Pb2+ (9.2·105 µA/µM) and outstanding limits of detection (97 fM, signal-to-noise ratio 3) for Pb2+, and remarkable for H2O2 (2.51 µM). The notable improvements were found to be favored by the increase in pyrolysis temperature. Multi-scale parameters such as (i) graphitization, densification of carbon support, and oxide nanoparticle reduction and purification were considered key aspects in the correlation between material properties and electrochemical response, followed by other effects such as (ii) average nanoparticle and Voronoi domain dimensions and (iii) average CXBiFe-T aggregate dimension.